Worker Characteristics and Dust Exposure to Pulmonary Function Status in Jumping Saw Division Of Wood Industry At Banyuwangi: An Association Study - Wulansari, Desy Tri (JURNAL KESEHATAN LINGKUNGAN, 2019)
Wood dust in the air will bring serious health problems if it is prolonged. Wood Dust has effect for health due to its effect on , pulmonary function via respiratory system entrance. The aim of this study was to analyze the association of worker characteristics and dust exposure to pulmonary function status in jumping saw division workers in wood industry Sempu, Banyuwangi. The research was observasional with cross sectional desain. Research data was obtained by giving questionnaire to respondent, measurement of dust level by using HVAS and lung physiology examination using spirometry tool. The sampel in this research was 7 workers in the part of jumping saw and 6 worker in the part of office. Data were analyzed with chi square statistical test to analyzing the association and statistical t-test to analyzing difference pulmonary function status between to 2 groups. The result showed that dust level in the exposure groups of jumping saw workers was 19,90 mg/m3 and non-exposure group (office) was 0,089 mg/m3, suitable with Permenakertrans No. 13/MEN/X/2011 is 5 mg/m3. Results of lung function measurement showed that normal 15,38% and impairment 84,62%. It is concluded that no associoation between age, length of employment, smoking habit, respiratory ptotective equipment usage habit, respiratory diseases history and dust exposure to pulmonary function status, except association between nutrion status with pulmonary function status. The company should monitor the levels of wood dust, to ensure that it does not exceed the NAB and regular lung physiological health checks.